Evaluating a heat-tolerant wheat germplasm in a heat stress environment - Sittichai Lordkaew (2019)
© NIAB 2019. Heat stress, a regular risk to wheat in the subtropics, is a growing threat in other wheat producing regions as the global temperature rises. This paper reports on three experiments evaluating 49 entries of the 13th High Temperature Wheat Yield Trial (13HTWYT) from the International Centre for Maize and Wheat Improvement (distributed in 2014), with Fang 60 as the local check, at two locations at Chiang Mai, Thailand, a designated representative of the wheat mega-environment 5, in which temperature for the coolest month averages >17.5 °C and the crop is subjected to high temperature for the entire growing season. The wheat was grown in the lowland (elevation 330 m) at Chiang Mai University in (i) sand culture to simulate the condition of non-limiting nutrient and water supply and (ii) in the field and (iii) as an on-farm trial in the highlands (elevation 800 m) at Mae Wang district of Chiang Mai province. Heat tolerance in the wheat germplasm, recently developed for adaptation to high temperature, was indicated by longer pre-heading duration, and the positive correlation between days to heading and grain yield all three experiments. The longer time before heading enabled development of larger spikes that produced more seeds from more and larger spikelets and more competent florets. However, with the number of spikes that was either lower than or similar to Fang 60, none of the recently developed 13HTWYT entries out-yielded the local check from the 1970s.